The sitter's impression: Memory and early modern portrait medallions - Howard, Rebecca M (Journal of material culture, 2019)
While the communicative nature of early modern Italian portraits becomes increasingly overt during the 15th and 16th centuries, the continued, and increasing, prevalence of the portrait medallion might at first seem to stand against the tide of period advances in creating portraits that engage with the viewer by looking out of the image. Although the portrait medallion, in its sculpted, metallic form, certainly creates a more physically-lasting work, the object's lack of a transitive, communicative sitter (as these sitters are nearly always in strict profile) might lead one to assume that the work is less capable of creating any such connection. Taking account of these things, this study challenges this assumption, examining the way that a portrait medallion, in its three-dimensionality, may actually provide a different, yet equally communicative, connection with the mind of a period viewer. Considering the Aristotelian belief that an image might be capable of impressing' itself in a viewer's memory - a belief re-examined in the late medieval and early modern periods - this article suggests that patrons of portrait medallions sought to make an impact on the beholder by way of the artwork's very form. Drawing from the belief that images impress themselves in the mind, as a seal impresses wax, this article adds to readings considering the appeal of portrait medallions in early modernity. By embodying a medium and genre of representation particularly equipped to produce memories, the portrait medallion could metaphorically stamp' itself on the beholder's mind, thereby working towards a primary goal of early modern portraiture - perpetually commemorating period sitters.